2012
DOI: 10.1007/s11481-012-9364-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Glutaminase Release Contributes to Glutamate-Mediated Neurotoxicity during Human Immunodeficiency Virus-1 Infection

Abstract: Human immunodeficiency virus (HIV) induces a neurological disease culminating in frank dementia referred to as HIV-associated dementia (HAD). Neurotoxins from HIV-1-infected and activated mononuclear phagocytes contribute to the neuropathogenesis of HAD. Glutamate is the predominant excitatory neurotransmitter in the mammalian central nervous system (CNS) and functions through activation of multiple receptors. Excessive glutamate production by HIV-infected macrophages in HAD may contribute to neuronal injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…Increase in glutamate levels has been reported to be glutamine-dependent, and the glutamatemediated neurotoxicity has been shown to be augmented by the mitochondrial glutaminase release. 17,20 Similar to these reports, we have observed a significant increase in the levels of GLS in the media by HIV-1 Vpr overexpression in macrophages (Fig. 4E) resulting in increased extracellular release of glutamate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Increase in glutamate levels has been reported to be glutamine-dependent, and the glutamatemediated neurotoxicity has been shown to be augmented by the mitochondrial glutaminase release. 17,20 Similar to these reports, we have observed a significant increase in the levels of GLS in the media by HIV-1 Vpr overexpression in macrophages (Fig. 4E) resulting in increased extracellular release of glutamate.…”
Section: Discussionsupporting
confidence: 89%
“…17,20 We hypothesize that the observed increase in extracellular levels of glutamate in the context of HIV-1 infection of macrophages is mediated by Vpr induced glycolysis, and TCA cycle activation in HIV-1 infected macrophages. To test this hypothesis we employed U937 cells activated by phorbol-12-myristate-13-acetate (PMA), to promote cell cycle arrest and induction of a differentiation program into macrophages, characterized by phenotypic and functional changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutaminase has been implicated in the neurotoxic effect of various CNS cell types in vitro , including macrophages, microglia (Huang et al, 2011; Tian et al, 2012; Zhao et al, 2004), and neurons (Hoffman et al, 2016; Ye et al, 2013). Furthermore, glutamianse is associated with various neurodegenerative and neuroinflammatory disesases such as HIV-1 associated dementia, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer's disease (Burbaeva et al, 2014; D'Alessandro et al, 2011; Huang et al, 2011; Werner et al, 2001; Zhao et al, 2012), as well as neuropsychiatric diseases such as schizophrenia (Gluck et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Even in cART treated individuals, certain populations of HIV-infected macrophages transmigrate into the CNS and can be found in perivascular cuffs and in parenchyma (Langford et al, 2003; Gras and Kaul, 2010; Buckner et al, 2011). These infected monocytes have altered metabolic functions that increase the release of immunomodulatory factors and amino acids such as arachidonic acid and glutamate (Tian et al, 2012; Koenig et al, 1986; Dreyer and Lipton, 1995; Yadav and Collman, 2009; Yao et al, 2010; Thompson et al, 2011). The removal of viral and proteinaceous components from the media of HIV-infected macrophages (HIV/MDM) revealed that a low molecular weight compounds acting through glutamatergic receptors were toxic to neurons (O'Donnell et al, 2006; Erdmann et al, 2007; Erdmann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%